The Analysis of Students’ Politeness In Interaction on Facebook at the Fourth Semester Students of the English Education Program of Stkip Taman Siswa Bima - Wulandary Putri Buana Sakti; Ramli (STKIP Taman Siswa Bima, 2019)
The aims of this research are: (1) The politeness used by students of fourth semester at STKIP Taman Siswa Bima in interaction on social networking Facebook. (2)The factors influenced students’ politeness in interaction. This research investigates how are the politeness used by students in their interaction in Basecamp group on Facebook. This research is descriptive research; This research used the primary data taken by the scrip of the students’ interaction on Facebook that will be analyzed in this research. Also, researcher used recording of interview. The result of this research showed that there were 62 Extracts among 9 conversations used by students, the researcher found 15 were used Bald on Record, 26 used Positive Politeness, 15 used Negative Politeness, and 6 used Off-record. Positive politeness was dominated among other kinds of politeness, which is oriented by the speaker toward the positive face or the positive self-image of the hearer that the speaker claims for himself. The speaker can satisfy the addressee’s positive face wants by emphasizing that speaker wants what the hearer’s wants. The use of Bald-on record which is chosen by students also. By using this politeness, the addressee possible to easy catch the speaker mean, so misunderstanding can be avoided. Only a very small number of participants are applying off-record. The second result that there are 3 factors that influenced students’ politeness at the students fourth semester of English Education Program of STKIP Taman Siswa Bima. The factors are : (1)Social Statues, students use polite utterances when they speak to theirs lecturers; (2) Situation; students use polite utterances depend on formal and informal situation, and (3) Gender, there are different utterances of female and male students and when they talk each others. Male students use polite utterances when they talk to female students because they have sensitive feeling